The Chinese Translation Study of the Cognitive Reserve Index Questionnaire - Cao, Ting; Zhang, Shifang; Yu, Mingming; Zhao, Xiaoyan; Wan, Qiaoqin (Frontiers in Psychology, 2022)
Purpose: To perform the translation and adaption of Cognitive Reserve Index questionnaire into Chinese and assess the reliability of the Chinese version. Materials and methods: The Chinese version of Cognitive Reserve Index questionnaire was created from a standard forward-backward translation. A total of 371 volunteers, aged between 20 and 89 years, participated in this survey. Participants were divided into three age-groups (Young, Middle-aged, Elderly), and subgroup differences were examined by independent samples t-tests, ANOVA analysis as well as post-hoc analysis. Pearson correlation analysis was applied to test the association between the total scores and each subscore (CRI-Education, CRI-WorkingActivity and CRI-LeisureTime). The internal consistency and test-retest reliability of Cognitive Reserve Index questionnaire were assessed. The test-retest reliability was measured among 40 participants with a two-week interval using intraclass correlation coefficient. Results: Strong correlations were observed between the total scores and each subscore (CRI-Education, CRI-WorkingActivity and CRI-LeisureTime: r = 0.65, 0.79 and 0.70, respectively). In contrast, it was found low to moderate correlations among three subscores. The internal consistency was acceptable (Cronbach’s alpha coefficient = 0.68). The intraclass correlation coefficient for total scores of the Chinese version of Cognitive Reserve Index questionnaire was 0.87 (95% CI 0.74 ~ 0.93). Conclusions: The Chinese version of Cognitive Reserve Index questionnaire was a potentially reliable and practical tool for evaluating cognitive reserve accumulated through a person’s lifespan.